A Tale of Two Cities: Understanding Children's Cycling Behavior From the Socio-Ecological Perspective - Yesiltepe, Demet; Pepping, Rian; Ling, Fiona Chun Man; Tempest, Gavin; Mauw, Steven; Janssen, Mirka; Hettinga, Florentina (Frontiers in Public Health, 2022)
The childhood obesity epidemic has persisted for over three decades, which has presented serious social, economic and health consequences worldwide. For researchers and policy makers alike, cycling has been a promising focus over recent years for developing long-term physically active lifestyles in urban environments, in addition to contributing to the global quest to combat climate change. Promoting cycling thus presents a win-win situation not just for individuals' well-being, but for multiple involved sectors such as public health, transport ministry and environmental agencies. For children, cycling promotes exercise engagement, active transport opportunities, motor skill development and social interaction. However, across European cities, there are considerable discrepancies in the uptake of cycling amongst children. To understand and subsequently promote children's cycling behavior, it is crucial that the complex social, physical and policy environment, and their interrelationships, are considered. Therefore, in this perspective article, we adopt the socio-ecological model to gain insight into how children's cycling behavior is shaped at the interpersonal, organizational and community level embedded within city policies, relevant to increase future cycling participation in children. Our perspective is based on a review of cycling policies of two European cities, Amsterdam (Netherlands) and Newcastle (UK), where stark contrasts in children's cycling participation can be observed. Our findings show that cycling policies in Amsterdam have mainly contributed to comprehensive organizational level changes, for example, cycling infrastructure development within the city, whereby these initiatives have made significant progress at the community level where cycling has become part of the “Dutch culture”. Hence, cycling is a more common transportation mode among children in Amsterdam than in Newcastle. In Newcastle, policies primarily focus on organizational or community level changes, and progress has recently been accelerated in response to COVID-19. In addition to differences, we have also identified similar challenges in the two cities, such as the urgency to support uptake of cycling for children with low socio-economic background or challenges related to cultural differences. We also propose a “shared (cycle-)path” for policy makers and researchers as working together is crucial in producing multi-component interventions at a policy level that recognize individual, as well as interpersonal, community and organizational factors.